Analisis Manajemen Risiko Pada UMKM “Mie Ayam Mas Adi” Bandung - Arrachman, Hajar Chair; Karimah, Nur Rafidah; Rahmawati, Siti (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Businesses that are currently developing are small businesses, where the business does not require a lot of capital, and the process of setting it up is easy. Small businesses are business activities that have small initial capital, small assets, and a small number of workers. It can be said that a small business is an individual business or legal entity that carries out simple economic activities with the aim of making a profit within certain limits. Traders are one of the micro and medium enterprises whose implementation requires relatively small capital and usually uses their own capital or loans.